(untitled) (Simbiótica. Revista Eletrônica, 2023)
In this article we interpret the 2008 testimony “Soldados não choram” in its relations with society, institutional politics and social movements that, in the 21st century, challenged traditional myths of masculinity. The military environment, portrayed in the text, presents itself as a complicated context for the couple of protagonists, soldiers who, when assuming their own homosexuality, faced numerous retaliations. The rigidity of formal, military, religious and family education also contributed to complicate the future of the protagonist Fernando who, based on his memories and experiences, describes the oppression of patriarchy in a global perspective and elaborates proposals for change towards a more humane, less violent, and democratic Brazil.